Kepemimpinan Pendidikan Berbasis Uswatun Hasanah: Menjadikan Kepala Sekolah sebagai Role Model Karakter di Era Digital - Siswadi, Siswadi (Pusat Riset dan Inovasi Nasional, 2024)
The world of education is currently undergoing a massive digital transformation that is not only changing learning methods but also shifting the values ​​and ethics within the school environment. The character crisis, such as cyberbullying and the degradation of morality, demands the emergence of leaders capable of serving as moral compasses amidst technological disruption. This study aims to explore the actualization of the Uswatun Hasanah concept by school principals as a character-strengthening strategy in the digital era. The research method used was qualitative with a library research approach. Data were collected through relevant literature, including the Quran (specifically Surah Al-Ahzab: 21), books, and research journals on digital education transformation. The results indicate that Uswatun Hasanah-based leadership positions the principal's personal integrity as a